Green Tourism as a New Direction for Sustainable Tourism Development: Policy and Implementation in Angantelu Traditional Village (Bukit Batu Belah) - Brahmandika, Pande Gede (Politeknik Negeri Bali, 2024)
Angantelu Traditional Village, with its natural and cultural riches, has great potential to implement green tourism as a sustainable tourism development strategy. Bukit Batu Belah, as one of the tourist destinations in this village, offers beautiful natural panoramas and opportunities for various environmentally friendly activities such as jogging and hiking. This research aims to examine the concept and implementation of green tourism as a new direction for the development of sustainable tourism in the Angantelu Traditional Village. A qualitative approach is used to understand the context, meaning and experiences of research subjects holistically. Data collection was carried out through in-depth interviews, observation and documentation studies. Data analysis was carried out using a qualitative approach, such as narrative and thematic analysis. This result showed that the implementation of green tourism in the Angantelu Traditional Village, especially in Bukit Batu Belah, has shown various successes and challenges. The green tourism policies and programs implemented have succeeded in increasing environmental awareness and active participation of local communities. Conservation efforts and land use regulations have helped preserve local ecosystems, while environmental education programs strengthen public and tourist understanding of the importance of sustainable tourism. However, the main challenges faced include a lack of coordination between stakeholders, environmental awareness that still needs to be improved, and conflicts of interest between tourism actors and the community.